Microeconomical analysis of roof decks market in Poland - Barnas Katarzyna (My University, 2006)
The main goal of this thesis paper is to perform a macroeconomic and microeconomic analysis on the roof covering market in Poland and try to recognize the position of one of the largest suppliers – Matizol. This analysis is going to be performed first of all by looking at some basic definitions to better explain the issues later discussed. This thesis deals with the overall performance of the Polish economy in the past 15 years to allow for a better understanding of building industry stance and prospects, and within it – a sector of roof coverings in which Matizol operates. The empirical part of this thesis is based on vast field studies performed during the largest building industry fair in Central Europe held in Poznan in February 2006. More than a dozen companies which are found in the market for roof covering products were surveyed and the gathered information allowed for positioning Matizol in several dimensions. Chapter one explains what is a market, the supply and demand of it. It also presents the term of the product, its attributes and the life cycle and it places the product within different type of markets, such as monopolistic or perfect competition. Chapter two presents the macroeconomic analysis of the situation in Poland. The time span that has been taken into account is of the past 15 years. This chapter looks at all the actors that influence the way the economy operates. Most importantly it analyzes the construction sector, which is crucial for the positioning of Matizol. Chapter three presents the results of the study that was performed in Poznan. It gives a thorough explanation of both the questions and the answers that were presented in the survey. The chapter gives an analysis of Matizol and positions it among other companies on the market.
Analiza mikroekonomiczna rynku pokryć dachowych w Polsce
Keywords: market; product; demand; marketing-mix; supply; life cycle of a product